‘Seeing’ the electromagnetic spectrum: spotlight on the cryptochrome photocycle - Aguida, Blanche; Babo, Jonathan; Baouz, Soria; Jourdan, Nathalie; Procopio, Maria; El-Esawi, Mohamed A.; Engle, Dorothy; Mills, Stephen; Wenkel, Stephan; Huck, Alexander; Berg-Sørensen, Kirstine; Kampranis, Sotirios C.; et al. (Frontiers in Plant Science, 2024)
Cryptochromes are widely dispersed flavoprotein photoreceptors that regulate numerous developmental responses to light in plants, as well as to stress and entrainment of the circadian clock in animals and humans. All cryptochromes are closely related to an ancient family of light-absorbing flavoenzymes known as photolyases, which use light as an energy source for DNA repair but themselves have no light sensing role. Here we review the means by which plant cryptochromes acquired a light sensing function. This transition involved subtle changes within the flavin binding pocket which gave rise to a visual photocycle consisting of light-inducible and dark-reversible flavin redox state transitions. In this photocycle, light first triggers flavin reduction from an initial darkadapted resting state (FADox). The reduced state is the biologically active or 'lit' state, correlating with biological activity. Subsequently, the photoreduced flavin reoxidises back to the dark adapted or 'resting' state. Because the rate of reoxidation determines the lifetime of the signaling state, it significantly modulates biological activity. As a consequence of this redox photocycle Crys respond to both the wavelength and the intensity of light, but are in addition regulated by factors such as temperature, oxygen concentration, and cellular metabolites that alter rates of flavin reoxidation even independently of light. Mechanistically, flavin reduction is correlated with conformational change in the protein, which is thought to mediate biological activity through interaction with biological signaling partners. In addition, a second, entirely independent signaling mechanism arises from the cryptochrome photocycle in the form of reactive oxygen species (ROS). These are synthesized during flavin reoxidation, are known mediators of biotic and abiotic stress responses, and have been linked to Cry biological activity in plants and animals. Additional special properties arising from the cryptochrome photocycle include responsivity to electromagnetic fields and their applications in optogenetics. Finally, innovations in methodology such as the use of Nitrogen Vacancy (NV) diamond centers to follow cryptochrome magnetic field sensitivity in vivo are discussed, as well as the potential for a whole new technology of 'magneto-genetics' for future applications in synthetic biology and medicine.